A comparative study on MEMS piezoelectric microgenerators - Md Ralib @ Md Raghib, Aliza 'Aini; Nordin, Anis Nurashikin; Salleh, Hanim (Springer Berlin / Heidelberg, 2010)
The growing demand of wireless sensor networks has created the necessity of miniature, portable, long lasting and easily recharged sources of power. Traditional, hazardous batteries are rendered unacceptable and the viability of ‘green’ MEMS energy harvesters has become even more dominant. This paper reviews the state-of-theart MEMS piezoelectric energy harvesters which promise a cleaner environment and eliminate the disposal issue of conventional batteries. Piezoelectric devices are the perfect candidate for implementation in micro generators as they are easily fabricated, are silicon compatible and demonstrate high efficiencies for mechanical to electrical energy conversion. The characteristic equations which govern the conversion of mechanical vibration to electrical power are described in this paper. The typical operating modes for MEMS piezoelectric energy cantilevers which are namely; d31 and d33 are also detailed. Criteria for optimum material suitable for MEMS energy scavengers to produce maximum power output are also outlined. Several MEMS energy harvesters which have been successfully fabricated and tested are also critically reviewed in this paper. Finally a comparison table highlighting the advantages and disadvantages of each work is presented.